2018
DOI: 10.1177/2041731418788509
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous structuring and mineralization of silk fibroin scaffolds

Abstract: Silk fibroin is commonly used as scaffold material for tissue engineering applications. In combination with a mineralization with different calcium phosphate phases, it can also be applied as material for bone regeneration. Here, we present a study which was performed to produce mineralized silk fibroin scaffolds with controlled macroporosity. In contrast to former studies, our approach focused on a simultaneous gelation and mineralization of silk fibroin by immersion of frozen silk fibroin monoliths in acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…As reported in the literature of Roedel et al, at the same time of mineralization, a sol-to-gel transition was also induced because of the pH of the solution (resulting from the presence of Ca ions). This was accompanied by a more stable β-sheet form inside the nanofiber, which resulted in higher mechanical properties . In addition, the interfacial bonding between SF nanofiber and mineral coating could lead to a more potent stiffening effect, which is also directly positively correlated with the amount of mineral …”
Section: Resultsmentioning
confidence: 88%
“…As reported in the literature of Roedel et al, at the same time of mineralization, a sol-to-gel transition was also induced because of the pH of the solution (resulting from the presence of Ca ions). This was accompanied by a more stable β-sheet form inside the nanofiber, which resulted in higher mechanical properties . In addition, the interfacial bonding between SF nanofiber and mineral coating could lead to a more potent stiffening effect, which is also directly positively correlated with the amount of mineral …”
Section: Resultsmentioning
confidence: 88%
“…Unidirectionally frozen using a dry ice/ethanol slurry and freeze-dried Anisotropic Investigating novel materials relevant for cardiac tissue engineering; study improved tissue infiltration and cellular proliferation by incorporating ECM material into processed solution [16] Silk fibroin cryogel Unidirectionally frozen between two differently cooled tempered Peltier elements; cross-linked by thawing in acidic calcium phosphate solution Anisotropic Developing protocols for the fabrication of mineralized silk; experimental conditions yielded scaffolds with uniformly aligned pores and inlet diameters ranging from 30 to 50 µm [34] Silk fibroin sponge Silk fibroin solution of different concentrations and molecular weights frozen at − 20 °C and then freeze-dried Isotropic Using silk fibroin as a representative polymer to investigate the effect polymer concentration and molecular weight have on sponge pore morphology and mechanical properties [12] Collagen-nanohydroxyapatite (nanoHA) cryogel Gelled in − 18 °C and thawed at room temperature; washed scaffolds were then freeze-dried; scaffolds had varying compositions of collagen and nanoHA Isotropic Investigated as novel biomaterial for bone tissue engineering; study demonstrated different compositions of collagen:nanoHA affected tissue infiltration and cell proliferation, with a 30:70 composition, functioning best compared to 100:0 and 50:50 compositions [35] Silk fibroin sponges with microchannels Silk fibroin solution cast around linear wire arrays (508 µm ϕ and 1 mm gap) and frozen at − 20 °C and then freeze-dried Isotropic Augmenting standard silk fibroin sponges with a set of microchannels to demonstrate that microchannels improve mass transfer across scaffold and tissue infiltration [36] Chitosan scaffolds Gelled chitosan solution frozen at − 80 °C and freezedried; dried scaffolds were cut to size and then loaded with plasmid DNA encoding perlecan domain I and VEGF189…”
Section: Anisotropicmentioning
confidence: 99%
“…The mineralization of scaffolds can further potentiate the osteogenesis process [ 65 ], however, contradictory results were demonstrated by Munhoz et al (2018), who reported that the mineralization of collagen and chitosan sponges did not stimulate bone neoformation sufficiently for tissue repair [ 66 ]. However, it must be considered that the experimental procedure was performed on the calvaria of rats, which is not subject to biomechanical load by muscle action.…”
Section: Discussionmentioning
confidence: 99%